Après le monde : Antoinette Rychner et la fin de la métaphore cynégétique - Laurence Perron (Itinéraires)
With Après le Monde, Antoinette Rychner depicts an imminent post-apocalyptic future where patriarchal institutions and over-exploitation of natural resources have led to a foreseeable environmental and economic disaster, as a resultant of the logic of capitalism. Throughout this paper, I will explore how Rychner uses ecofeminist premises as the driving force of the narrative (in this case, a post-apocalyptic / science fiction narrative) by both relying on and extending Ursula K. Le Guin ecocriticism concept of “carrier bag theory of fiction.” I will therefore highlight how Rychner borrows from the “carrier bag” form by building her narrative around the bardesses and their epic tales, and how this link manages to resemiotize the fictional, social and environmental spaces, allowing the protagonists to reintroduce their experience within it.